Future trends of the export demand for selected Malaysian cocoa products - Abdel Hameed, Amna Awad; Mohamed Arshad, Fatimah (Academic Journals, 2014)
Cocoa products’ trade is very important to the Malaysian economy and the global cocoa industry. Therefore, this study aims to identify the main factors that shape the export demand for selected Malaysian cocoa products and to make project the trends of the demand for them. It uses annual data over the period 1980-2012 to investigate the export demand for Malaysian cocoa powder and cocoa butter. Two single equation models are specified, to represent each of the cocoa products. The models have been estimated using multivariate cointegration and Error Correction methods for the analysis, through utilizing the Augmented Autoregressive Distributed Lag technique. The long-run income elasticities obtained by estimating the models have been incorporated into a projection framework to forecast the cocoa products export demand. The findings of the study show that the most sequential factor affecting the Malaysian cocoa products export demand is the world level of income, followed by their own prices. Coconut oil emerged to be the main substitute for the Malaysian cocoa butter which is also highly sensitive to the world population growth. The long horizon forecasting reveal expected upward trends in the export demand of both commodities.